2013
DOI: 10.3389/fmicb.2013.00364
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lincomycin resistance genes associated with lincomycin residues in waters and soils adjacent to representative swine farms in China

Abstract: Lincomycin is commonly used on swine farms for growth promotion as well as disease treatment and control. Consequently, lincomycin may accumulate in the environment adjacent to the swine farms in many ways, thereby influencing antibiotic resistance in the environment. Levels of lincomycin-resistance genes and lincomycin residues in water and soil samples collected from multiple sites near wastewater discharge areas were investigated in this study. Sixteen lincomycin-resistance and 16S rRNA genes were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
4
15
2
Order By: Relevance
“…Furthermore, results for resistance gene detection, as shown in this study, were also consistent to those observed by Munir & Xagoraraki (2011). The abundance of Inu F resistance gene in this study was lower than those observed by Cheng et al (2013); Li et al (2013). Detection of aph (3')-IIIa and bla TEM in this study were similar to those observed by Sun et al (2014).…”
Section: Aph(2″)lb Aph(2″)-lc Aph(2″)-ld Aph(3″)-llla Ant(4')-la Vanasupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, results for resistance gene detection, as shown in this study, were also consistent to those observed by Munir & Xagoraraki (2011). The abundance of Inu F resistance gene in this study was lower than those observed by Cheng et al (2013); Li et al (2013). Detection of aph (3')-IIIa and bla TEM in this study were similar to those observed by Sun et al (2014).…”
Section: Aph(2″)lb Aph(2″)-lc Aph(2″)-ld Aph(3″)-llla Ant(4')-la Vanasupporting
confidence: 89%
“…Polymerase chain reaction with specific oligonucleotide primers was used to determine the presence/occurrence of antibiotic resistance Li et al (2013) TA B L E 1 (Continued) genes (ARG) in isolates that showed multidrug resistance to the antibiotics tested. The detection of 26 ARGs targets cutting across different classes of antibiotics tested was analyzed following a previous protocol described by Hsu, Wang, Chen, Lu, & Chen (2007).…”
Section: Pcr Amplification Assays For the Detection Of Antibiotic Rmentioning
confidence: 99%
“…The observations from this study differed from those observed by Faldynova et al (2013) because aadA resistance gene was not detected in all isolates and sul1 and sul2 resistance genes were more or less equally observed in isolates from soil samples in pig farm. In a study conducted by Li et al (2013), they observed an abundance of InuF resistance gene in all soil samples collected in pig farm and this was not the case in this study as InuF resistance gene was less detected in soil samples from pig farm. Similar results reported by Li et al (2013) were also reported by Cheng et al (2013) where widespread of InuF resistance gene was also observed in soil samples proximal to pig farm.…”
Section: Sul1 Sul2contrasting
confidence: 67%
“…In a study conducted by Li et al (2013), they observed an abundance of InuF resistance gene in all soil samples collected in pig farm and this was not the case in this study as InuF resistance gene was less detected in soil samples from pig farm. Similar results reported by Li et al (2013) were also reported by Cheng et al (2013) where widespread of InuF resistance gene was also observed in soil samples proximal to pig farm.…”
Section: Sul1 Sul2contrasting
confidence: 67%
“…Isolates containing ermC were in the low-G + C content group. ErmC was not detected in water or soil collected from wastewater trenches exporting waste from a swine farm (Li et al, 2013). ErmC was detected in hog house effluent by Chen et al (2007), but less frequently than the five other erm genes screened for in the study.…”
Section: Discussionmentioning
confidence: 63%